USULAN PERBAIKAN TERHADAP MANAJEMEN PERAWATAN DENGAN MENGGUNAKAN METODE TOTAL PRODUCTIVE MAINTENANCE (TPM) DI PT. SNA MEDIKA - Cahya, Fajar; Pusakaningwati, Ayik (Journal Knowledge Industrial Engineering (JKIE), 2018)
Total Productive Maintenance (TPM) is a system of maintenance and repair of machines or equipment involving all divisions and employees ranging from operators to top management based on mutually agreed commitments. The methodology used in writing this thesis uses field studies, namely by making observations and direct research on machine maintenance systems at PT. SNA Medika, while the purpose of this paper is to conduct an analysis of the maintenance management system of the doomby shuttle loom machine that is applied at PT. SNA Medika and provide suggestions for improvement of the maintenance system by implementing a preventive system using the maintenance method of Total Productive Maintenance (TPM) consisting of total effectiveness variables, and calculating and analyzing the total effectiveness variables contained in the TPM system by using the TPM Index method. Implementation of the maintenance system or treatments that refer to the application of the 5R work culture are less effective. This is indicated by the still high rate of engine failure, high engine downtime, and low values ​​of effectiveness, such as the effectiveness of machine availability (AV), production effectiveness (PE), effectiveness of quality level (RQ), and overall effectiveness of machines and equipment ( OEE). Through the analysis of the Cause and Effect diagram, it can be seen that the overall effectiveness of the machine is still 64% (not yet meeting the JIPM standard,> 85%). Therefore a production machine maintenance program is made using the TPM method, which consists of maintenance by the operator and the formation of small group activities (AKK).